Variation of boza nutrition parameters based on raw materials - Novák, Anna; Kovács, Béla; Czipa, Nikolett (Acta Agraria Debreceniensis, 2016)
Boza is a ceral based fermented drink. Raw material of boza could be rise, millet, wheat and rye. Because of the diversity of raw materilas and the method of fermentation boza might show varied quality and nutrition value.Nowadays healthy and conscious nutrition are playing more and more important roles in our lives. People pay an ever growing attention to the nutrition value of products, such as protein- and sugar content, components with antioxidant properties, and the mineral content of the products. In our research we wanted to know how the protein,-, sugar-, total polifenol-, mikro- and macro element content of products change.